Kegiatan Donor Darah Di Restoran Ayam Penyet Cindelaras Berastagi Bekerjsama Dengan PMI Kabupaten Karo - Daniel Ginting; Farida Ariani Pelawi; Nina Fentiana (FKIP, Universitas Palangka Raya, 2024)
Blood donation activities are carried out to maintain the stability of the blood stock of PMI Karo Regency. The blood donation activity will be held on Sunday, November 16 2023 starting at 09.30 WIB at the Ayam Penyet Cindelaras Berastagi Restaurant. The blood donation service activity was attended by a total of 20 participants. From the results of the activity, 14 bags of blood were collected. Based on interviews with the participants, their motivation for donating blood was due to a sense of humanity for people in need, to maintain their own health, invitations from friends, and some were interested because of the gifts offered at the end of the event. The implementation of this blood donation activity as part of community service has been carried out well and received a good response from the participants. More outreach is needed so that the number of blood donors increases and more people are willing to become blood donors.